2010
DOI: 10.1016/j.neulet.2010.07.083
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive findings on the morphology of dendritic spines in the rat medial amygdala

Abstract: The rat posterodorsal medial amygdala (MePD) is a brain area in which gonadal hormones induce notable plastic effects in the density of dendritic spines. Dendritic spines are post-synaptic specializations whose shape and spacing change neuronal excitability. Our aim was to obtain new data on the dendritic spines morphology and density from MePD neurons using the carbocyanine dye DiI under confocal microscopy. In adult male rats, the dendritic spine density of the medial branches of the left MePD (mean+/-SD) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 44 publications
1
37
0
2
Order By: Relevance
“…These neurons are connected to specific hypothalamic nuclei and appear to modulate reproduction [82]. This homogeneity among MePD neurons might explain the low variability in soma size, soma volume, and dendritic spine density density described previously [30,37,65,78,83,84].…”
Section: Morphological Features Of the Medial Amygdalamentioning
confidence: 65%
See 4 more Smart Citations
“…These neurons are connected to specific hypothalamic nuclei and appear to modulate reproduction [82]. This homogeneity among MePD neurons might explain the low variability in soma size, soma volume, and dendritic spine density density described previously [30,37,65,78,83,84].…”
Section: Morphological Features Of the Medial Amygdalamentioning
confidence: 65%
“…No single morphological characteristic is used to reliably identify these neurons [17,18,37,[78][79][80][81][82][83][84][85] Though gonadal hormone receptors are not present in all cells in the neural regions, the classic Golgi method cannot distinguish neurons that concentrate sex steroids from those that do not [78,81]. However, confocal immunofluorescent microscopy has revealed that transcription factor Lhx6-immunoreactive cells constitute approximately 80% of all neurons in the MePD [82].…”
Section: Morphological Features Of the Medial Amygdalamentioning
confidence: 99%
See 3 more Smart Citations